Endoscopic Transpapillary Gallbladder Drainage for Acute Cholecystitis using Two Gallbladder Stents (Dual Gallbladder Stenting) - Zain A Sobani; Sergio A. Sánchez-Luna; Tarun Rustagi (Korean Society of Gastrointestinal Endoscopy, 2021)
Background/Aims Endoscopic transpapillary gallbladder drainage (ETPGBD) is gaining popularity for the management of acute cholecystitis (AC) in high-risk patients. However, the stents placed during the procedure are not immune to obstruction. Here we describe a novel technique of stenting with two transpapillary stents and evaluate its technical feasibility, safety, and efficacy in AC. Methods A retrospective analysis of all patients undergoing ETPGBD using dual stents for AC at our institution between November 1, 2017 and August 31, 2020 was conducted. We abstracted patient data to evaluate technical and clinical success, adverse events, and long-term outcomes. Two stents were placed either during the index procedure or during an interval procedure performed 4-6 weeks after the index procedure. Results A total of 21 patients underwent ETPGBD with dual stenting (57.14% male, mean age: 62.14±17.21 years). The median interval between the placement of the first and the second stents was 37 days (range: 0-226 days). Technical and clinical success rates were 100%, with a recurrence rate of 4.76% (n=1) and adverse event rate of 9.52% (n=2) during a mean follow-up period of 471.74±345.64 days (median: 341 days, range: 55-1084 days). Conclusions ETPGBD with dual gallbladder stenting is a safe and effective technique for long-term gallbladder drainage in non-surgical candidates. Larger controlled studies are needed to validate our findings for the widespread implementation of this technique.